The Extent of the Practice of Administrative Leaders to Transformational Leadership: A Field Study on the Workers at The General Organization for Grain Silos and Flour Mills in Saudi Arabia - Alshammari, Abdulrahman; Alsultan, Nada (The Arab Journal of Administration, 2018)
The aim of this study to identify the extent of the practice of administrative leaders at the General Organization for Grain Silos and Flour Mills in Saudi Arabia of transformational leadership، from the employees’ point of view based on the transformational leadership dimensions, which are being a good role model، inspiring others، encouraging creativity، and concern for individual members. The study population consisted of all employees in the organization of silos and flourmills except for administrative leadership positions. The questionnaire was distributed to 226 of the employees. The study provided several findings among them: the administrative leadership of the General Organization for Grain Silos and Flour Mills exercises transformational leadership» four dimensions significantly. The study made a number of recommendations including: more attention to transformational leadership and its applications in organizations because of its significant impact on motivating employees and on finding out the best way to deal with employees and manage them to achieve organizational efficiency and effectiveness objectives. The study also recommended training leaders in the Grain Silos and Flour Mills to be more effectiveness in achieving the objectives of the institution and more able to influence the staff they have.